An assessment of female participation in minor irrigation systems of Sri Lanka - Molen, I. van der (International Water Management Institute, 2001)
Analyses the participation of female farmers in the farmer organizations (FO) of minor irrigation systems and identifies factors that hamper the participation of women in decision-making processes with regard to land, cultivation and irrigation. The paper argues that participation does not necessarily result in equity and that other forms of equity interact with gender inequity in the FOs.